The current situation and influential factors of bottom-up technology transmission in Chinese rural families - Nan, Wu; Siti Ezaleila Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
With the rapid development of science and technology and the drastic changes of society, the digital generation gap has a negative impact on intergenerational relationships. To help the older generation integrate into the digital world and narrow the digital generation gap within families, this study investigated the current situation of three-generation bottom-up technology transmission in Chinese rural families and explored the factors related to this process. Using the questionnaire survey, we surveyed 436 samples of 79 families in China, including 197 grandparents, 122 parents and 117 children. The results show that most of the older generation learn to use WeChat from the younger generation. Although the grandparents’ adoption and use of digital media are significantly lower than those of the parents, they are significantly more receptive to bottomup technology transmission than the parents. Furthermore, bottom-up technology transmission is mainly related to the demographic characteristics, subjective feelings, psychological expectations, degree of interaction and intimacy of family members. The more vulnerable individuals (older, less educated, female, less self-efficacy and more psychological disorders), the more likely they are to receive bottom-up technology transmission. The findings emphasized the important influence of mediated communication and intimacy in bottom-up technology transmission in Chinese rural families.